Kebijakan Bupati dalam Meminimalisasi Resistensi dalam Kepemimpinannya di Kabupaten Banyuwangi 2005-2009 - Lestari, Ratna Ani (Universitas Brawijaya, Indonesia, 2010)
The focus of the study is the said resistance, both in latent and manifest modes. By applying qualitative methods, it is hypothesized that the resistance occur in latent and manifest modes. Results of the research show that, first, the modes of resistance of local political elites to the regent's policies were based on certain economical and political motives. Second, the mode of resistance is either latent (obscure) or manifest (open). Third, in reducing the resistance the regent implemented three policy models, (a) democratic policy model, (b) situational policy model, and (c) participatory innovative policy model, which was implemented as free education, free healthcare services, and free ID card. These innovations were proven to be effective in reducing the resistance.Keywords: Regent's policies, latent-manifest resistance, innovative policy.